THE RESETTLEMENT OF POPULATION OF THE DNEPROPETROVSK CITY: HUMAN-GEOGRAPHICAL FEATURES - Гусєва, Наталія; Суптело, Ольга (Human Geography Journal, 2016)
The article deals with characteristics of the territorial population distribution of the Dnepropetrovsk city. The general characteristic of the population settlement of the Dnepropetrovsk city are given. The population density by administrative districts of the Dnepropetrovsk city is calculated and analyzed. The index of population concentration are reduced and characterized. The application center-graphical method by territorial characteristics in the research of population settlement is founded. The methodical foundations spatial-statistical analysis of population distribution is shown. The arithmetic mean, median and modal center are calculated. Theirs contents and meanings are given. The results are displayed cartographical. The spatial and statistical features of the population distribution on the territory of the Dnepropetrovsk city are identified and analyzed.